Anti-collision strip for freight elevator, mounting method and application of anti-collision strip

By using a combined design of soft PVC material and integral rigid metal brackets in the anti-collision strip of the cargo elevator, the problem of local stress and installation complexity during impact is solved, and a more uniform impact force dispersion and Higher appearance aesthetics, while improving the mechanical properties and weather resistance of the material.

CN119284693AActive Publication Date: 2025-01-10HUZHOU DONGSU ELEVATOR PARTS
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411446273.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-10
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The anti-collision strips for traditional cargo elevators are partially concentrated when impacted, resulting in damage to the car wall, complex installation and low efficiency, unsightly appearance, and the material is sensitive to environmental factors, which affects the installation accuracy and appearance cleanliness.

Method used

Using anti-collision strip made of soft PVC material, combined with the design of the integrated rigid metal bracket and self-tapping and self-drilling screws, the bracket disperses the impact force on the entire anti-collision strip, and there is no screw hole on the outer surface, simplifying installation and improving appearance. Aesthetics, while improving the mechanical properties and weather resistance of the material through specific modified fillers and additives.

Benefits of technology

Effectively disperse impact force, reduce wall damage, simplify the installation process, improve appearance cleanliness, reduce installation failure risk, improve the mechanical properties and durability of the material, and ensure the stability and reliability of the product in long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284693A_ABST
    Figure CN119284693A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-collision strip for a freight elevator, an installation method and application of the anti-collision strip, and belongs to the technical field of anti-collision strip preparation technologies, the anti-collision strip comprises a body made of a soft PVC material, and the material is prepared through a specific formula and technology so as to enhance the mechanical property and weather resistance of the anti-collision strip. The body is designed to be free of screw holes, the appearance is kept clean and attractive, and hanging is facilitated through the chamfer design. The anti-collision strip is installed on a support made of a galvanized sheet, and the support is provided with a bolt installation hole and a self-tapping and self-drilling screw so as to fix an anti-collision strip body. When collision occurs, the support can disperse impact force to the whole anti-collision strip, and damage to the elevator car wall is reduced. Compared with the prior art, the anti-collision strip is reasonable in structural design, easy and convenient to install and attractive in appearance, the safety of the freight elevator can be effectively improved, and the service life of the freight elevator can be effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation technology of anti-collision strips, and in particular to an anti-collision strip for a freight elevator, an installation method and application thereof. Background Art

[0002] In the field of freight elevators, anti-collision strips are important components to protect the elevator car wall from damage caused by cargo impact. However, the traditional anti-collision strip design has some limitations, which bring a series of problems in practical applications.

[0003] In early designs, the anti-collision strips for freight elevators were usually installed by punching holes throughout the strip. This design brings the following major problems: Local concentrated force: Traditional anti-collision strips are designed as flexible components and are installed and fixed by punching holes. When a collision occurs, the impact force is often concentrated on a few installation points, causing the car wall at the force points or local areas to be easily damaged. This local concentrated force not only reduces the protective effect of the anti-collision strips, but also may accelerate the wear and damage of the elevator car wall. Unstable installation hole size: Soft PVC materials are sensitive to environmental factors. For example, changes in temperature and humidity may cause the material to expand or contract, which in turn affects the size of the preset hole positions. This makes it possible that the installation holes reserved by the elevator manufacturer on the car wall may not match the actual hole positions of the anti-collision strips, resulting in the anti-collision strips cannot be installed correctly. To solve this problem, it is usually necessary to re-drill holes on site according to the actual hole positions of the PVC parts, which not only increases the complexity of installation, but also prolongs the construction time. Damaged appearance: In the traditional anti-collision strip design, the installation screws are exposed on the outer surface of the anti-collision strip, which not only affects the appearance of the interior of the elevator, but may also become an obstacle to cleaning and maintenance. Exposed screws may also hook onto packaging materials during cargo handling, causing unnecessary damage. Low processing efficiency: Traditional methods for processing countersunk mounting holes on PVC parts usually rely on manual operations or inefficient mechanical processing, which results in low processing dimensional accuracy and low production efficiency. This inefficient processing method increases production costs and also limits the scale and automation of anti-collision strip production.

[0004] In view of the above problems, the market urgently needs a new anti-collision strip design for freight elevators, which can provide more uniform impact force dispersion, simplify the installation process, improve the appearance neatness, and improve processing efficiency.

[0005] In the prior art, Chinese invention patent CN104351988A discloses a connection process of PVC anti-collision strip and nitrile gloves, comprising the following steps: (1) placing the manufactured PVC anti-collision strip in an aluminum mold; (2) punching the hot melt adhesive film into the size and shape of the anti-collision strip in step (1) with a copper knife mold; (3) attaching the hot melt adhesive film punched in step (2) to the anti-collision strip described in step (1); (4) placing the aluminum mold under the pressing plate of the high-frequency machine, and putting the nitrile gloves on the hand mold; (5) adjusting the current and working time of the high-frequency machine, pressing the on button, the high-frequency machine head is pressed down to the mold, the current instantly increases the temperature of the pressing plate, the hot melt adhesive undergoes shape reshaping, and the anti-collision strip and the nitrile gloves are connected together. This invention replaces the traditional sewing process, reduces equipment investment, and greatly improves work efficiency. The PVC anti-collision strip of the labor protection gloves produced is firmly bonded and not easy to fall off; and the production purpose of low cost and high output is achieved. However, the PVC anti-collision strip of the invention has poor mechanical properties and low aging resistance. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention aims to provide an anti-collision strip for a freight elevator having better performance, easier installation and more beautiful appearance, an installation method and applications thereof.

[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0008] An anti-collision strip for a freight elevator, comprising:

[0009] A. An anti-collision strip body 1 made of soft PVC material;

[0010] B. A bracket 2, used to support the anti-collision strip body 1;

[0011] C. The anti-collision strip body 1 is provided with a chamfer to facilitate hanging from the upper end to the bracket 2;

[0012] D. The bracket 2 is provided with a bolt 3 mounting hole and a self-drilling screw 4 for fixing the anti-collision strip body 1;

[0013] E. When the anti-collision strip body 1 is hit, the bracket 2 can disperse the impact force to the entire anti-collision strip body 1.

[0014] The bracket 2 is an integral rigid structure, and when hit, the impact force can be dispersed to the entire anti-collision strip body 1.

[0015] The outer surface of the anti-collision strip body 1 has no screw holes to keep the overall appearance neat and beautiful.

[0016] The bracket 2 is made of 1-3 mm thick galvanized sheet.

[0017] The method for installing the anti-collision strip for a freight elevator comprises the following steps:

[0018] (1) Fix the bracket 2 with bolts 3;

[0019] (2) Hang the anti-collision strip body 1 from the upper end downward onto the bracket 2;

[0020] (3) Tighten the self-drilling screws 4 to fix the anti-collision strip body 1;

[0021] (4) When a collision occurs, the impact force is dispersed to the entire anti-collision strip body 1 through the bracket 2.

[0022] The preparation method of the soft PVC material is as follows, in parts by weight:

[0023] S1. Mix 2-4 parts of polyethylene oxide, 1-3 parts of nylon 66, 0.2-0.4 parts of epoxidized soybean oil and 0.01-0.03 parts of tri(2-ethylhexyl) phosphate in a premixing device for 20-40 minutes; then, raise the temperature to 70-80° C., add 0.01-0.03 parts of butylated hydroxyanisole at this temperature, and continue stirring until the component is completely dissolved;

[0024] S2, then, add 8 to 12 parts of PVC resin into the premixing equipment, and stir at a speed of 100 to 300 rpm, and gradually increase the temperature to 70 to 90°C; in this process, add 0.05 to 0.2 parts of zinc stearate, 0.1 to 0.3 parts of dibutyltin dilaurate, 0.4 to 0.6 parts of modified filler, 0.1 to 0.3 parts of brominated polystyrene, 0.2 to 0.4 parts of sodium bicarbonate, 0.05 to 0.2 parts of stearamide, 0.05 to 0.2 parts of sorbitol, 0.4 to 0.6 parts of di-tert-butyl peroxide and 0.1 to 0.3 parts of inorganic pigment in sequence, control the flow direction of the materials, ensure uniform mixing, and obtain a premixed material;

[0025] S3, adding the premixed material into the reaction vessel by spraying; then, raising the temperature in the reaction vessel to 130-150° C., and transferring the material to a cooling device by high-speed stirring at 400-600 rpm;

[0026] S4, the material is stirred in the cooling equipment and cooled to room temperature before being taken out; the cooled material is sent to the planetary extruder and extruded under the temperature control of 130-150°C; the extruded material enters the calender and is calendered at a temperature of 180-200°C to form a sheet; finally, the calendered sheet is cooled to room temperature, and is rolled and packaged.

[0027] The inorganic pigment is at least one of titanium dioxide, red iron oxide, chromium oxide green and white carbon black.

[0028] The preparation method of the modified filler is as follows, in parts by weight:

[0029] Z1. After 0.5-2 parts of montmorillonite are pounded to remove sand, 0.005-0.02 parts of potassium chloride and 0.01-0.03 parts of magnesium carbonate are added; heating is carried out under high-speed stirring conditions at a heating rate of 4-6°C / min to 800-950°C for 10-30 minutes to obtain calcined montmorillonite;

[0030] Z2, cooling the calcined montmorillonite to 65-75° C., adding 0.005-0.02 parts of a titanate coupling agent and 0.005-0.02 parts of palmitic acid, respectively, stirring for 10-30 minutes to obtain a mixture; adding the mixture to a high-speed mixer at 50-70° C., adding 0.05-0.2 parts of methacrylic acid and 0.001-0.003 parts of azobisisobutyronitrile, stirring for 2-4 hours; raising the mixer temperature to 120-140° C., stirring at high speed for 1-3 hours to obtain pretreated montmorillonite;

[0031] Z3, dissolving 0.1-0.3 parts of sodium lauryl sulfate and 0.01-0.03 parts of 2,4,6-trihydroxybenzoic acid in 0.8-1.2 parts of polyphosphoric acid, reacting at 180-220° C. for 4-6 hours; cooling to room temperature, washing with acetone, filtering, and drying at 80-120° C. for 5-15 hours to obtain a grafting agent;

[0032] Z4. Mix 0.8-1.2 parts of pretreated montmorillonite, 0.2-0.4 parts of grafting agent and 0.005-0.02 parts of carbon fiber in a high-speed mixer at 80-120° C. for 1-3 hours, and cool to room temperature to obtain a modified filler.

[0033] The anti-collision strip for a freight elevator is used to provide protection on the car wall of the freight elevator to reduce the impact damage to the elevator wall that may be caused during the transportation of goods and to improve operational safety.

[0034] In the present invention, the functions of each substance are as follows:

[0035] Soft PVC material, as the main component of the anti-collision strip body, provides basic physical properties such as flexibility and impact resistance.

[0036] Polyethylene oxide is used as a plasticizer or compatibilizer in the preparation of PVC materials to improve processing performance and flexibility.

[0037] Nylon 66 may be used as a reinforcing material to improve the mechanical strength and heat resistance of PVC.

[0038] Epoxidized soybean oil acts as a plasticizer or stabilizer, which helps to improve the flexibility and aging resistance of PVC materials.

[0039] Tri(2-ethylhexyl) phosphate is used as a plasticizer or processing aid to improve the processing properties of PVC.

[0040] Butylated hydroxyanisole is used as an antioxidant to improve the heat-oxidative aging resistance of PVC materials.

[0041] Zinc stearate acts as a stabilizer to prevent thermal decomposition of PVC during processing and use.

[0042] Dibutyltin dilaurate is used as a heat stabilizer for PVC to improve the thermal stability and weather resistance of the material.

[0043] Modified fillers improve the mechanical properties of PVC materials, such as strength, stiffness, aging resistance and wear resistance.

[0044] Brominated polystyrene may be used as a flame retardant to improve the flame retardant properties of PVC materials.

[0045] Sodium bicarbonate may be used as a pH regulator or foaming agent in the preparation of PVC materials.

[0046] Stearamide acts as a lubricant to improve the processing properties of PVC materials.

[0047] Sorbitol acts as a plasticizer to improve the flexibility and processing properties of PVC materials.

[0048] Di-tert-butyl peroxide is used as a cross-linking agent to increase the cross-linking density of PVC materials and enhance their mechanical properties.

[0049] Inorganic pigments (titanium dioxide, red iron oxide, chromium oxide green, and white carbon black) provide color and hiding power, and improve the weather resistance and stability of PVC materials.

[0050] Montmorillonite, as the main component of modified filler, provides reinforcement effect.

[0051] Potassium chloride and magnesium carbonate may act as flux or promoter during montmorillonite calcination.

[0052] Titanate coupling agent is used as a surface modifier of montmorillonite to improve its compatibility with PVC matrix and the reinforcing effect.

[0053] Palmitic acid may act as a coupling agent or lubricant to improve the compatibility of montmorillonite with PVC.

[0054] Methacrylic acid may act as a grafting agent in montmorillonite pretreatment to enhance the chemical bonding between montmorillonite and PVC.

[0055] Sodium lauryl sulfate and 2,4,6-trihydroxybenzoic acid may be used as reactants in the preparation of grafting agents and used to synthesize grafting agents with specific functions.

[0056] Polyphosphoric acid is used as a solvent or reaction medium in the synthesis of the grafting agent.

[0057] Carbon fiber is used as a reinforcing material for modified fillers to improve the mechanical strength and heat resistance of PVC materials.

[0058] The combination and interaction of these substances make the anti-collision strip of the present invention have good mechanical properties and weather resistance, while maintaining a good appearance and ease of installation.

[0059] Compared with the prior art, it has the following beneficial effects:

[0060] 1) The new anti-collision strip of the present invention adopts an integrally rigid metal bracket, which can more effectively disperse the impact force to the entire anti-collision strip when it is hit, thereby reducing local damage to the car wall.

[0061] 2) The new design of the present invention allows the elevator factory to reserve installation holes on the car wall, so that the construction site can be directly installed without the need to process the installation holes on site, which simplifies the installation process and improves efficiency.

[0062] 3) The outer surface of the anti-collision strip body of the present invention has no screw holes, and adopts the method of hook connection and self-drilling screws, which makes the appearance more neat and beautiful, and reduces the risk of damage caused by exposed screws.

[0063] 4) The design of the new anti-collision strip of the present invention reduces the problem of PVC part hole size changes caused by environmental factors, reducing the risk of installation failure. In addition, the design of self-drilling screws makes replacement and removal more convenient, improving the convenience of maintenance.

[0064] 4) The soft PVC material of the present invention provides a material with optimized physical properties and processing properties, achieving a significant improvement in the mechanical properties and weather resistance of the material, so that the manufactured anti-collision strip maintains flexibility and impact resistance while also showing better durability and reliability. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 The utility model relates to an anti-collision strip for a freight elevator of the present invention.

[0066] In the figure: 1. Anti-collision strip body; 2. Bracket; 3. Bolt; 4. Self-drilling screw.

[0067] Figure 2 It is a bolt installation hole in the anti-collision strip for the freight elevator of the present invention.

[0068] Figure 3 When installing the anti-collision strip for a freight elevator of the present invention, the bracket is first fixed, and the soft PVC material is hung from the upper end downward on the bracket. The soft PVC material has chamfers for easy hanging.

[0069] Figure 4 When the anti-collision strip for a freight elevator of the present invention is installed, the bottom screws are tightened after hanging. DETAILED DESCRIPTION

[0070] Polyethylene oxide: average molecular weight: 100,000, purchased from Merck.

[0071] Nylon 66: molecular weight ≥ 226.14, purchased from Merck.

[0072] Epoxidized soybean oil: single product number: 104654, main use: PVC plasticizer, Jinan Luying Chemical Co., Ltd.

[0073] PVC resin: Model: SG-3, Wenzhou Zhengbang Chemical Co., Ltd.

[0074] Brominated polystyrene: Product model: BPS, Wuhan Huaxiang Kejie Biotechnology Co., Ltd.

[0075] Montmorillonite: Item No.: gc-006, Shijiazhuang Gaocheng New Material Technology Co., Ltd.

[0076] Titanate coupling agent: single product number: NDZ-201, Dongguan Dinghai Plastic Chemical Co., Ltd.

[0077] Aluminate coupling agent: Product model: coupling agent DL-411, Dongguan Kangjin New Material Technology Co., Ltd.

[0078] Silane coupling agent: Product model: coupling agent KH-550, Henan Lichi Fine Chemical Co., Ltd.

[0079] Kaolin: Product number: AB-12, mesh number: 1250 mesh, Shijiazhuang Anbai Mining Co., Ltd.

[0080] Talc: Item No.: 08, Shandong Taijun Industry and Trade Co., Ltd.

[0081] Polyphosphoric acid: CAS No.: 8017-16-1, Jinan Huifengda Chemical Co., Ltd.

[0082] Carbon fiber: Article number: 021563, thickness: 7-13μm, length: 3-50mm, Jiangsu Kangdafu New Material Technology Co., Ltd.

[0083] Carbon nanotubes: Model: NACODC8, length ≤10μm, tube diameter: 40-60nm, Jiaxing Bona New Materials Co., Ltd.

[0084] Graphene: Model: LN-1P, Fineness: 2000 mesh, Zhengzhou Kaichi Chemical Products Co., Ltd.

[0085] The remaining raw materials in the examples and comparative examples of the present invention are all commercially available products.

[0086] The design idea of ​​the present invention is to combine the excellent physical properties of soft PVC materials and the strengthening effect of specific modified fillers to develop a cargo elevator anti-collision strip with ingenious structural design, simple installation, and the ability to effectively disperse and absorb impact force when impacted. The neat appearance and practicality of the product are achieved through the carefully designed bracket structure and the screw-free appearance of the anti-collision strip body. At the same time, the safety and durability of the anti-collision strip in actual use are improved through the design of the reinforcement column. In addition, by using specific modified fillers, the mechanical properties and weather resistance of the material are further improved, ensuring the stability and reliability of the anti-collision strip in long-term use.

[0087] Example 1

[0088] An anti-collision strip for a freight elevator, comprising:

[0089] A. A bumper strip body 1 made of soft PVC material, the outer surface of which has no screw holes to keep the whole body neat and beautiful;

[0090] B. A bracket 2, which is made of a 2.0 mm thick galvanized sheet and is used to support the anti-collision strip body 1. The bracket 2 is an integral rigid structure and can disperse the impact force to the entire anti-collision strip body 1 when it is hit;

[0091] C. The anti-collision strip body 1 is provided with a chamfer to facilitate hanging from the upper end to the bracket 2;

[0092] D. The bracket 2 is provided with a bolt 3 mounting hole and a self-drilling screw 4 for fixing the anti-collision strip body 1;

[0093] E. When the anti-collision strip body 1 is hit, the bracket 2 can disperse the impact force to the entire anti-collision strip body 1.

[0094] The method for installing the anti-collision strip for a freight elevator comprises the following steps:

[0095] (1) Fix the bracket 2 with bolts 3;

[0096] (2) Hang the anti-collision strip body 1 from the upper end downward onto the bracket 2;

[0097] (3) Tighten the self-drilling screws 4 to fix the anti-collision strip body 1;

[0098] (4) When a collision occurs, the impact force is dispersed to the entire anti-collision strip body 1 through the bracket 2.

[0099] The preparation method of the soft PVC material is as follows:

[0100] S1. In a premixing device, 3 kg of polyethylene oxide, 2 kg of nylon 66, 0.3 kg of epoxidized soybean oil and 0.02 kg of tri(2-ethylhexyl) phosphate are mixed for 30 minutes; then, the temperature is raised to 75° C., and 0.02 kg of butylated hydroxyanisole is added at this temperature, and stirring is continued until the component is completely dissolved;

[0101] S2, then, add 10kg PVC resin into the premixing equipment, and stir at a speed of 200 rpm, and gradually increase the temperature to 80°C; in this process, add 0.1kg zinc stearate, 0.2kg dibutyltin dilaurate, 0.5kg modified filler, 0.2kg brominated polystyrene, 0.3kg sodium bicarbonate, 0.1kg stearamide, 0.1kg sorbitol, 0.5kg di-tert-butyl peroxide and 0.2kg titanium dioxide in sequence, control the flow direction of the materials, ensure uniform mixing, and obtain a premixed material;

[0102] S3, adding the premixed material into the reaction vessel by spraying; then, raising the temperature in the reaction vessel to 140° C., and transferring the material to a cooling device by high-speed stirring at 500 rpm;

[0103] S4. The material is stirred in the cooling equipment and cooled to room temperature before being taken out; the cooled material is sent to the planetary extruder and extruded under the temperature control of 140°C; the extruded material enters the calender and is calendered at a temperature of 190°C to form a sheet; finally, the calendered sheet is cooled to room temperature, and is rolled and packaged.

[0104] The preparation method of the modified filler is as follows:

[0105] Z1. After 1 kg of montmorillonite is pounded and sanded, 0.01 kg of potassium chloride and 0.02 kg of magnesium carbonate are added; the mixture is heated under high-speed stirring at a heating rate of 5°C / min to 900°C for 20 minutes to obtain calcined montmorillonite;

[0106] Z2, cooling the calcined montmorillonite to 70°C, adding 0.01kg of titanate coupling agent and 0.01kg of palmitic acid respectively, stirring for 20 minutes to obtain a mixture; adding the mixture to a high-speed mixer at 60°C, adding 0.1kg of methacrylic acid and 0.002kg of azobisisobutyronitrile, stirring for 3 hours; raising the mixer temperature to 130°C, stirring at high speed for 2 hours, to obtain pretreated montmorillonite;

[0107] Z3, dissolving 0.2 kg sodium lauryl sulfate and 0.02 kg 2,4,6-trihydroxybenzoic acid in 1 kg polyphosphoric acid, reacting at 200° C. for 5 hours; cooling to room temperature, washing with acetone, filtering, and drying at 100° C. for 10 hours to obtain a grafting agent;

[0108] Z4. Mix 1 kg of pretreated montmorillonite, 0.3 kg of grafting agent and 0.01 kg of carbon fiber in a high-speed mixer at 100° C. for 2 hours, and cool to room temperature to obtain a modified filler.

[0109] Example 2

[0110] An anti-collision strip for a freight elevator is substantially the same as that in Example 1, the only difference being that the preparation method of the modified filler is different.

[0111] The preparation method of the modified filler is as follows:

[0112] Z1. After 1 kg of kaolin is pounded and sanded, 0.01 kg of potassium chloride and 0.02 kg of magnesium carbonate are added; the mixture is heated under high-speed stirring at a heating rate of 5°C / min to 900°C for 20 minutes to obtain calcined kaolin;

[0113] Z2, cooling the calcined kaolin to 70°C, adding 0.01kg of titanate coupling agent and 0.01kg of palmitic acid respectively, stirring for 20 minutes to obtain a mixture; adding the mixture to a high-speed mixer at 60°C, adding 0.1kg of methacrylic acid and 0.002kg of azobisisobutyronitrile, stirring for 3 hours; raising the mixer temperature to 130°C, stirring at high speed for 2 hours, to obtain pretreated kaolin;

[0114] Z3, dissolving 0.2 kg sodium lauryl sulfate and 0.02 kg 2,4,6-trihydroxybenzoic acid in 1 kg polyphosphoric acid, reacting at 200° C. for 5 hours; cooling to room temperature, washing with acetone, filtering, and drying at 100° C. for 10 hours to obtain a grafting agent;

[0115] Z4. Mix 1 kg of pretreated kaolin, 0.3 kg of grafting agent and 0.01 kg of carbon fiber in a high-speed mixer at 100° C. for 2 hours, and cool to room temperature to obtain a modified filler.

[0116] The installation method of the anti-collision strip for a freight elevator is the same as that of Example 1.

[0117] The preparation method of the soft PVC material is the same as that of Example 1.

[0118] Example 3

[0119] An anti-collision strip for a freight elevator is substantially the same as that in Example 1, the only difference being that the preparation method of the modified filler is different.

[0120] The preparation method of the modified filler is as follows:

[0121] Z1. After 1 kg of talc powder is pounded and sanded, 0.01 kg of potassium chloride and 0.02 kg of magnesium carbonate are added; the mixture is heated under high-speed stirring at a heating rate of 5°C / min to 900°C for 20 minutes to obtain calcined talc powder;

[0122] Z2, the calcined talc was cooled to 70 ° C, 0.01 kg of titanate coupling agent and 0.01 kg of palmitic acid were added respectively, and stirred for 20 minutes to obtain a mixture; the mixture was added to a high-speed mixer at 60 ° C, 0.1 kg of methacrylic acid and 0.002 kg of azobisisobutyronitrile were added, and stirred for 3 hours; the mixer temperature was raised to 130 ° C, and stirred at high speed for 2 hours to obtain pretreated talc;

[0123] Z3, dissolving 0.2 kg sodium lauryl sulfate and 0.02 kg 2,4,6-trihydroxybenzoic acid in 1 kg polyphosphoric acid, reacting at 200° C. for 5 hours; cooling to room temperature, washing with acetone, filtering, and drying at 100° C. for 10 hours to obtain a grafting agent;

[0124] Z4. Mix 1 kg of pretreated talc powder, 0.3 kg of grafting agent and 0.01 kg of carbon fiber in a high-speed mixer at 100° C. for 2 hours, and cool to room temperature to obtain a modified filler.

[0125] The installation method of the anti-collision strip for a freight elevator is the same as that of Example 1.

[0126] The preparation method of the soft PVC material is the same as that of Example 1.

[0127] Example 4

[0128] An anti-collision strip for a freight elevator is substantially the same as that in Example 1, the only difference being that the preparation method of the modified filler is different.

[0129] The preparation method of the modified filler is as follows:

[0130] Z1. After 1 kg of montmorillonite is pounded and sanded, 0.01 kg of potassium chloride and 0.02 kg of magnesium carbonate are added; the mixture is heated under high-speed stirring at a heating rate of 5°C / min to 900°C for 20 minutes to obtain calcined montmorillonite;

[0131] Z2, cooling the calcined montmorillonite to 70°C, adding 0.01kg of aluminate coupling agent and 0.01kg of palmitic acid respectively, stirring for 20 minutes to obtain a mixture; adding the mixture to a high-speed mixer at 60°C, adding 0.1kg of methacrylic acid and 0.002kg of azobisisobutyronitrile, stirring for 3 hours; raising the mixer temperature to 130°C, stirring at high speed for 2 hours, to obtain pretreated montmorillonite;

[0132] Z3, dissolving 0.2 kg sodium lauryl sulfate and 0.02 kg 2,4,6-trihydroxybenzoic acid in 1 kg polyphosphoric acid, reacting at 200° C. for 5 hours; cooling to room temperature, washing with acetone, filtering, and drying at 100° C. for 10 hours to obtain a grafting agent;

[0133] Z4. Mix 1 kg of pretreated montmorillonite, 0.3 kg of grafting agent and 0.01 kg of carbon fiber in a high-speed mixer at 100° C. for 2 hours, and cool to room temperature to obtain a modified filler.

[0134] The installation method of the anti-collision strip for a freight elevator is the same as that of Example 1.

[0135] The preparation method of the soft PVC material is the same as that of Example 1.

[0136] Example 5

[0137] An anti-collision strip for a freight elevator is substantially the same as that in Example 1, the only difference being that the preparation method of the modified filler is different.

[0138] The preparation method of the modified filler is as follows:

[0139] Z1. After 1 kg of montmorillonite is pounded and sanded, 0.01 kg of potassium chloride and 0.02 kg of magnesium carbonate are added; the mixture is heated under high-speed stirring at a heating rate of 5°C / min to 900°C for 20 minutes to obtain calcined montmorillonite;

[0140] Z2, the calcined montmorillonite was cooled to 70°C, 0.01kg of silane coupling agent and 0.01kg of palmitic acid were added respectively, and stirred for 20 minutes to obtain a mixture; the mixture was added to a high-speed mixer at 60°C, 0.1kg of methacrylic acid and 0.002kg of azobisisobutyronitrile were added, and stirred for 3 hours; the mixer temperature was raised to 130°C, and stirred at high speed for 2 hours to obtain pretreated montmorillonite;

[0141] Z3, dissolving 0.2 kg sodium lauryl sulfate and 0.02 kg 2,4,6-trihydroxybenzoic acid in 1 kg polyphosphoric acid, reacting at 200° C. for 5 hours; cooling to room temperature, washing with acetone, filtering, and drying at 100° C. for 10 hours to obtain a grafting agent;

[0142] Z4. Mix 1 kg of pretreated montmorillonite, 0.3 kg of grafting agent and 0.01 kg of carbon fiber in a high-speed mixer at 100° C. for 2 hours, and cool to room temperature to obtain a modified filler.

[0143] The installation method of the anti-collision strip for a freight elevator is the same as that of Example 1.

[0144] The preparation method of the soft PVC material is the same as that of Example 1.

[0145] Example 6

[0146] An anti-collision strip for a freight elevator is substantially the same as that in Example 1, the only difference being that the preparation method of the modified filler is different.

[0147] The preparation method of the modified filler is as follows:

[0148] Z1. After 1 kg of montmorillonite is pounded and sanded, 0.01 kg of potassium chloride and 0.02 kg of magnesium carbonate are added; the mixture is heated under high-speed stirring at a heating rate of 5°C / min to 900°C for 20 minutes to obtain calcined montmorillonite;

[0149] Z2, cooling the calcined montmorillonite to 70°C, adding 0.01kg of titanate coupling agent and 0.01kg of palmitic acid respectively, stirring for 20 minutes to obtain a mixture; adding the mixture to a high-speed mixer at 60°C, adding 0.1kg of methacrylic acid and 0.002kg of azobisisobutyronitrile, stirring for 3 hours; raising the mixer temperature to 130°C, stirring at high speed for 2 hours, to obtain pretreated montmorillonite;

[0150] Z3, dissolving 0.2 kg sodium lauryl sulfate and 0.02 kg 2,4,6-trihydroxybenzoic acid in 1 kg polyphosphoric acid, reacting at 200° C. for 5 hours; cooling to room temperature, washing with acetone, filtering, and drying at 100° C. for 10 hours to obtain a grafting agent;

[0151] Z4. Mix 1 kg of pretreated montmorillonite, 0.3 kg of grafting agent and 0.01 kg of carbon nanotubes in a high-speed mixer at 100° C. for 2 hours, and cool to room temperature to obtain a modified filler.

[0152] The installation method of the anti-collision strip for a freight elevator is the same as that of Example 1.

[0153] The preparation method of the soft PVC material is the same as that of Example 1.

[0154] Example 7

[0155] An anti-collision strip for a freight elevator is substantially the same as that in Example 1, the only difference being that the preparation method of the modified filler is different.

[0156] The preparation method of the modified filler is as follows:

[0157] Z1. After 1 kg of montmorillonite is pounded and sanded, 0.01 kg of potassium chloride and 0.02 kg of magnesium carbonate are added; the mixture is heated under high-speed stirring at a heating rate of 5°C / min to 900°C for 20 minutes to obtain calcined montmorillonite;

[0158] Z2, cooling the calcined montmorillonite to 70°C, adding 0.01kg of titanate coupling agent and 0.01kg of palmitic acid respectively, stirring for 20 minutes to obtain a mixture; adding the mixture to a high-speed mixer at 60°C, adding 0.1kg of methacrylic acid and 0.002kg of azobisisobutyronitrile, stirring for 3 hours; raising the mixer temperature to 130°C, stirring at high speed for 2 hours, to obtain pretreated montmorillonite;

[0159] Z3, dissolving 0.2 kg sodium lauryl sulfate and 0.02 kg 2,4,6-trihydroxybenzoic acid in 1 kg polyphosphoric acid, reacting at 200° C. for 5 hours; cooling to room temperature, washing with acetone, filtering, and drying at 100° C. for 10 hours to obtain a grafting agent;

[0160] Z4. Mix 1 kg of pretreated montmorillonite, 0.3 kg of grafting agent and 0.01 kg of graphene in a high-speed mixer at 100° C. for 2 hours, and cool to room temperature to obtain a modified filler.

[0161] The installation method of the anti-collision strip for a freight elevator is the same as that of Example 1.

[0162] The preparation method of the soft PVC material is the same as that of Example 1.

[0163] Comparative Example 1

[0164] A crash strip for a freight elevator is substantially the same as that in Example 1, the only difference being that the preparation method of the soft PVC material is different.

[0165] The preparation method of the soft PVC material is as follows:

[0166] S1. In a premixing device, 3 kg of polyethylene oxide, 2 kg of nylon 66, 0.3 kg of epoxidized soybean oil and 0.02 kg of tri(2-ethylhexyl) phosphate are mixed for 30 minutes; then, the temperature is raised to 75° C., and 0.02 kg of butylated hydroxyanisole is added at this temperature, and stirring is continued until the component is completely dissolved;

[0167] S2, then, add 10kg PVC resin to the premixing equipment, and stir at a speed of 200 rpm, and gradually increase the temperature to 80°C; in this process, add 0.1kg zinc stearate, 0.2kg dibutyltin dilaurate, 0.5kg montmorillonite, 0.2kg brominated polystyrene, 0.3kg sodium bicarbonate, 0.1kg stearamide, 0.1kg sorbitol, 0.5kg di-tert-butyl peroxide and 0.2kg titanium dioxide in sequence, control the flow direction of the materials, ensure uniform mixing, and obtain a premixed material;

[0168] S3, adding the premixed material into the reaction vessel by spraying; then, raising the temperature in the reaction vessel to 140° C., and transferring the material to a cooling device by high-speed stirring at 500 rpm;

[0169] S4. The material is stirred in the cooling equipment and cooled to room temperature before being taken out; the cooled material is sent to the planetary extruder and extruded under the temperature control of 140°C; the extruded material enters the calender and is calendered at a temperature of 190°C to form a sheet; finally, the calendered sheet is cooled to room temperature, and is rolled and packaged.

[0170] The installation method of the anti-collision strip for a freight elevator is the same as that of Example 1.

[0171] Comparative Example 2

[0172] A crash strip for a freight elevator is substantially the same as that in Example 1, the only difference being that the preparation method of the soft PVC material is different.

[0173] The preparation method of the soft PVC material is as follows:

[0174] S1. In a premixing device, 3 kg of polyethylene oxide, 2 kg of nylon 66, 0.3 kg of epoxidized soybean oil and 0.02 kg of tri(2-ethylhexyl) phosphate are mixed for 30 minutes; then, the temperature is raised to 75° C., and 0.02 kg of butylated hydroxyanisole is added at this temperature, and stirring is continued until the component is completely dissolved;

[0175] S2, then, add 10kg PVC resin into the premixing equipment, and stir at a speed of 200 rpm, and gradually increase the temperature to 80°C; in this process, add 0.1kg zinc stearate, 0.2kg dibutyltin dilaurate, 0.5kg kaolin, 0.2kg brominated polystyrene, 0.3kg sodium bicarbonate, 0.1kg stearamide, 0.1kg sorbitol, 0.5kg di-tert-butyl peroxide and 0.2kg titanium dioxide in sequence, control the flow direction of the materials, ensure uniform mixing, and obtain a premixed material;

[0176] S3, adding the premixed material into the reaction vessel by spraying; then, raising the temperature in the reaction vessel to 140° C., and transferring the material to a cooling device by high-speed stirring at 500 rpm;

[0177] S4. The material is stirred in the cooling equipment and cooled to room temperature before being taken out; the cooled material is sent to the planetary extruder and extruded under the temperature control of 140°C; the extruded material enters the calender and is calendered at a temperature of 190°C to form a sheet; finally, the calendered sheet is cooled to room temperature, and is rolled and packaged.

[0178] The installation method of the anti-collision strip for a freight elevator is the same as that of Example 1.

[0179] Comparative Example 3

[0180] A crash strip for a freight elevator is substantially the same as that in Example 1, the only difference being that the preparation method of the soft PVC material is different.

[0181] The preparation method of the soft PVC material is as follows:

[0182] S1. In a premixing device, 3 kg of polyethylene oxide, 2 kg of nylon 66, 0.3 kg of epoxidized soybean oil and 0.02 kg of tri(2-ethylhexyl) phosphate are mixed for 30 minutes; then, the temperature is raised to 75° C., and 0.02 kg of butylated hydroxyanisole is added at this temperature, and stirring is continued until the component is completely dissolved;

[0183] S2, then, add 10kg PVC resin into the premixing equipment, and stir at a speed of 200 rpm, and gradually increase the temperature to 80°C; in this process, add 0.1kg zinc stearate, 0.2kg dibutyltin dilaurate, 0.5kg talcum powder, 0.2kg brominated polystyrene, 0.3kg sodium bicarbonate, 0.1kg stearamide, 0.1kg sorbitol, 0.5kg di-tert-butyl peroxide and 0.2kg titanium dioxide in sequence, control the flow direction of the materials, ensure uniform mixing, and obtain a premixed material;

[0184] S3, adding the premixed material into the reaction vessel by spraying; then, raising the temperature in the reaction vessel to 140° C., and transferring the material to a cooling device by high-speed stirring at 500 rpm;

[0185] S4. The material is stirred in the cooling equipment and cooled to room temperature before being taken out; the cooled material is sent to the planetary extruder and extruded under the temperature control of 140°C; the extruded material enters the calender and is calendered at a temperature of 190°C to form a sheet; finally, the calendered sheet is cooled to room temperature, and is rolled and packaged.

[0186] The installation method of the anti-collision strip for a freight elevator is the same as that of Example 1.

[0187] Comparative Example 4

[0188] A crash strip for a freight elevator is substantially the same as that in Example 1, the only difference being that the preparation method of the soft PVC material is different.

[0189] The preparation method of the soft PVC material is as follows:

[0190] S1. In a premixing device, 3 kg of polyethylene oxide, 2 kg of nylon 66, 0.3 kg of epoxidized soybean oil and 0.02 kg of tri(2-ethylhexyl) phosphate are mixed for 30 minutes; then, the temperature is raised to 75° C., and 0.02 kg of butylated hydroxyanisole is added at this temperature, and stirring is continued until the component is completely dissolved;

[0191] S2, then, add 10kg PVC resin into the premixing equipment, and stir at a speed of 200 rpm, and gradually increase the temperature to 80°C; in this process, add 0.1kg zinc stearate, 0.2kg dibutyltin dilaurate, 0.2kg brominated polystyrene, 0.3kg sodium bicarbonate, 0.1kg stearamide, 0.1kg sorbitol, 0.5kg di-tert-butyl peroxide and 0.2kg titanium dioxide in sequence, control the flow direction of the materials, ensure uniform mixing, and obtain a premixed material;

[0192] S3, adding the premixed material into the reaction vessel by spraying; then, raising the temperature in the reaction vessel to 140° C., and transferring the material to a cooling device by high-speed stirring at 500 rpm;

[0193] S4. The material is stirred in the cooling equipment and cooled to room temperature before being taken out; the cooled material is sent to the planetary extruder and extruded under the temperature control of 140°C; the extruded material enters the calender and is calendered at a temperature of 190°C to form a sheet; finally, the calendered sheet is cooled to room temperature, and is rolled and packaged.

[0194] The installation method of the anti-collision strip for a freight elevator is the same as that of Example 1.

[0195] Test Example 1

[0196] Mechanical properties test: The tensile properties of soft PVC materials are tested in accordance with GB / T 1040.1-2018 "Determination of tensile properties of plastics Part 1: General". Test temperature:

[0197] 25℃; tensile rate: 50mm / min. Test three times and take the average value.

[0198] The test results are shown in Table 1.

[0199] Table 1

[0200]

[0201]

[0202] Test Example 2

[0203] Weathering test:

[0204] The soft PVC material prepared in the embodiment and the comparative example was made into a 1 mm soft film, then punched into a dumbbell shape, and put into an artificial aging tester. According to GB / T 16422.3-2022 "Plastic Laboratory Light Source Exposure Test Method Part 3: Aging Experiment with Fluorescent Ultraviolet Lamp", UVA-340, 10 h irradiation, 70 ° C, 5 h condensation, 40 ° C, no spraying, and aged for 720 h respectively for tensile strength test; the decline rate was calculated.

[0205] Decline rate = (tensile strength 老化前 -Tensile strength 老化后 ) / Tensile Strength 老化前 ×100%

[0206] The test results are shown in Table 2.

[0207] Table 2

[0208]

[0209]

[0210] It can be seen from test examples 1 to 2 that the soft PVC material obtained in Example 1 of the present invention has the best mechanical properties and weather resistance.

[0211] The reason why the montmorillonite used in Example 1 shows better mechanical properties and weather resistance than kaolin and talcum powder in the present invention may be because montmorillonite has a unique nano-layered structure, which can provide more contact area and better interfacial compatibility after appropriate calcination and organic modification, thereby achieving more effective stress dispersion and enhancement in the PVC matrix. The layered structure of montmorillonite can provide better interlayer slippage, absorb and delay crack propagation, and enhance the toughness of the material when subjected to stress. In addition, the high thermal stability and chemical properties of montmorillonite may make it easier to keep the structure intact during PVC processing, and then provide better weather resistance in long-term use. In contrast, kaolin and talcum powder may have certain limitations in compatibility, interlayer spacing and thermal stability, resulting in their effect being not as good as montmorillonite when reinforcing PVC materials.

[0212] In the present invention, Example 1 uses a titanate coupling agent to modify montmorillonite. Compared with the aluminate coupling agent used in Example 4 and the silane coupling agent used in Example 5, the obtained soft PVC material has better mechanical properties and weather resistance. This may be because the titanate coupling agent has higher reactivity and better compatibility, and can more effectively form chemical bonds with montmorillonite and PVC matrix, thereby improving interfacial adhesion and stress transfer efficiency. These characteristics of the titanate coupling agent help to form a more uniform stress distribution in the material, enhance the dispersibility of montmorillonite, reduce local stress concentration, and thus improve the overall mechanical properties of the material. At the same time, the titanate coupling agent may also help to improve the thermal stability and light stability of the material, further enhance the weather resistance of the material, so that the modified PVC can better maintain its performance during long-term use.

[0213] In the preparation of the modified filler of the present invention, the carbon fiber used in Example 1 shows better mechanical properties and weather resistance than the carbon nanotubes of Example 6 and the graphene of Example 7. This difference may be due to the unique structure and surface characteristics of carbon fiber. Carbon fiber has a high aspect ratio and excellent mechanical strength, and can form an effective stress transfer path in the PVC matrix, thereby improving the overall mechanical properties of the material. In addition, the chemical stability and UV stability of carbon fiber help to improve the weather resistance of PVC, so that it can still maintain good physical properties under long-term exposure to outdoor conditions. In contrast, although carbon nanotubes and graphene also have excellent mechanical and thermal properties, they may not be able to form the same efficient stress transfer mechanism with the PVC matrix as carbon fiber in the application of the present invention. This may be due to their dispersibility, compatibility with PVC or interface bonding effect in composite materials is not as ideal as carbon fiber. Therefore, when carbon fiber is used as a modified filler in the present invention, it provides better reinforcement effect and weather protection, thereby optimizing the comprehensive performance of the soft PVC material.

Claims

1. An anti-collision strip for a freight elevator, characterized in that: include: A. an anti-collision strip body (1) made of soft PVC material; B. a bracket (2) for supporting the anti-collision strip body (1); C. The anti-collision strip body (1) is provided with a chamfer to facilitate hanging from the upper end to the bracket (2); D. The bracket (2) is provided with bolt (3) mounting holes and self-drilling screws (4) for fixing the anti-collision strip body (1); E. When the anti-collision strip body (1) is hit, the impact force can be dispersed to the entire anti-collision strip body (1) through the bracket (2).

2. The anti-collision strip for a freight elevator according to claim 1, characterized in that: The bracket (2) is an integral rigid structure and can disperse the impact force to the entire anti-collision strip body (1) when impacted.

3. The anti-collision strip for a freight elevator according to claim 1, characterized in that: The outer surface of the anti-collision strip body (1) has no screw holes, so as to keep the overall appearance neat and beautiful.

4. The anti-collision strip for a freight elevator according to claim 1, characterized in that: The bracket (2) is made of a 1-3 mm thick galvanized sheet.

5. The anti-collision strip for a freight elevator according to claim 1, characterized in that: The preparation method of the soft PVC material is as follows, in parts by weight: S1. Mix 2-4 parts of polyethylene oxide, 1-3 parts of nylon 66, 0.2-0.4 parts of epoxidized soybean oil and 0.01-0.03 parts of tri(2-ethylhexyl) phosphate in a premixing device for 20-40 minutes; then, raise the temperature to 70-80° C., add 0.01-0.03 parts of butylated hydroxyanisole at this temperature, and continue stirring until the component is completely dissolved; S2, then, add 8 to 12 parts of PVC resin into the premixing equipment, and stir at a speed of 100 to 300 rpm, and gradually increase the temperature to 70 to 90°C; in this process, add 0.05 to 0.2 parts of zinc stearate, 0.1 to 0.3 parts of dibutyltin dilaurate, 0.4 to 0.6 parts of modified filler, 0.1 to 0.3 parts of brominated polystyrene, 0.2 to 0.4 parts of sodium bicarbonate, 0.05 to 0.2 parts of stearamide, 0.05 to 0.2 parts of sorbitol, 0.4 to 0.6 parts of di-tert-butyl peroxide and 0.1 to 0.3 parts of inorganic pigment in sequence, control the flow direction of the materials, ensure uniform mixing, and obtain a premixed material; S3, adding the premixed material into the reaction vessel by spraying; then, raising the temperature in the reaction vessel to 130-150° C., and transferring the material to a cooling device by high-speed stirring at 400-600 rpm; S4, the material is stirred in the cooling equipment and cooled to room temperature before being taken out; the cooled material is sent to the planetary extruder and extruded under the temperature control of 130-150°C; the extruded material enters the calender and is calendered at a temperature of 180-200°C to form a sheet; finally, the calendered sheet is cooled to room temperature, and is rolled and packaged.

6. The anti-collision strip for a freight elevator according to claim 5, characterized in that: The inorganic pigment is at least one of titanium dioxide, red iron oxide, chromium oxide green and white carbon black.

7. The anti-collision strip for a freight elevator according to claim 5, characterized in that: The preparation method of the modified filler is as follows, in parts by weight: Z1. After 0.5-2 parts of montmorillonite are pounded to remove sand, 0.005-0.02 parts of potassium chloride and 0.01-0.03 parts of magnesium carbonate are added; heating is carried out under high-speed stirring conditions at a heating rate of 4-6°C / min to 800-950°C for 10-30 minutes to obtain calcined montmorillonite; Z2, cooling the calcined montmorillonite to 65-75° C., adding 0.005-0.02 parts of a titanate coupling agent and 0.005-0.02 parts of palmitic acid, respectively, stirring for 10-30 minutes to obtain a mixture; adding the mixture to a high-speed mixer at 50-70° C., adding 0.05-0.2 parts of methacrylic acid and 0.001-0.003 parts of azobisisobutyronitrile, stirring for 2-4 hours; raising the mixer temperature to 120-140° C., stirring at high speed for 1-3 hours to obtain pretreated montmorillonite; Z3, dissolving 0.1-0.3 parts of sodium lauryl sulfate and 0.01-0.03 parts of 2,4,6-trihydroxybenzoic acid in 0.8-1.2 parts of polyphosphoric acid, reacting at 180-220° C. for 4-6 hours; cooling to room temperature, washing with acetone, filtering, and drying at 80-120° C. for 5-15 hours to obtain a grafting agent; Z4. Mix 0.8-1.2 parts of pretreated montmorillonite, 0.2-0.4 parts of grafting agent and 0.005-0.02 parts of carbon fiber in a high-speed mixer at 80-120° C. for 1-3 hours, and cool to room temperature to obtain a modified filler.

8. A method for installing the anti-collision strip for a freight elevator according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) fixing the bracket (2) with bolts (3); (2) Hanging the anti-collision strip body (1) from the upper end downward onto the bracket (2); (3) tightening the self-drilling screws (4) to fix the anti-collision strip body 1); (4) When a collision occurs, the impact force is dispersed to the entire anti-collision strip body (1) through the bracket (2).

9. An application of the anti-collision strip for a freight elevator as claimed in any one of claims 1 to 7, characterized in that: Provide protection on the car wall of the freight elevator to reduce the impact damage that may be caused to the elevator wall during cargo transportation and improve operational safety.

Citation Information

Patent Citations

  • Jointing technology of PVC bumper strip and butyronitrile gloves

    CN104351988A

  • Elastic buffer plastic wrapping membrane material and preparation method thereof

    CN107955253A

  • Wide-temperature-range flame retardant rubber powder-based thermal plastic elastomer damping material and preparation method thereof

    CN108485091A

  • Preparation method of high-elasticity weather-resistant PVC modified material

    CN111574787A

  • Elevator sedan -chair wall collision avoidance protective device

    CN205998820U